THE POSITION OF THE RUSSIAN GOVERNMENT TO THE ANGLO-BUR WAR - Sattorov Nurbek Abdurazzoqovich (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2020)
After the Republic of Uzbekistan gained its independence, there were great opportunities for changes in the political, socio-economic, cultural and educational life of the country. Under the leadership of the leadership of the republic, including President Mirziyoev Sh. He said, "Unfortunately, there are no forces that want to destabilize the situation in our society, around the world, around the world, to sow seeds of hatred, to cause conflicts and even bloodshed." We must remember the words and know that its roots go back to the late 19th and early 20th centuries. One of those wars was the British-Bur. As a result, many innocent people were killed. Many nations have reacted to this English war. One of such countries was the Russian Empire.